2005
DOI: 10.1016/j.foreco.2005.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparing composition and structure in old-growth and harvested (selection and diameter-limit cuts) northern hardwood stands in Quebec

Abstract: Single-tree selection cutting is sometimes believed to be similar to the natural gap disturbance regime of hardwood forests, but few studies have specifically compared the compositional and structural characteristics of old-growth hardwood stands, undergoing natural gap dynamics and hardwood stands previously subjected to partial cuts. This study characterized and compared the composition (saplings and trees) and structure (gaps, foliage distribution, tree diameter and density, snags and coarse woody debris) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
104
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 51 publications
14
104
0
Order By: Relevance
“…Even if differences between selection cutting and natural gap dynamics do exist (Angers et al 2005, Bauhus et al 2009), our study demonstrates that both SCt and SCp show promise in preserving important features of old-growth stands. Interestingly, even simple approaches that did not involve tree marking were able to maintain the main benefits of the treatment.…”
Section: Cprs Cpptm Sct Scp Control Key Old Forest Attributesmentioning
confidence: 78%
“…Even if differences between selection cutting and natural gap dynamics do exist (Angers et al 2005, Bauhus et al 2009), our study demonstrates that both SCt and SCp show promise in preserving important features of old-growth stands. Interestingly, even simple approaches that did not involve tree marking were able to maintain the main benefits of the treatment.…”
Section: Cprs Cpptm Sct Scp Control Key Old Forest Attributesmentioning
confidence: 78%
“…This was primarily the result of ingrowth from both natural regeneration and enrichment plantings under forest gaps. Many studies have already found that forest gaps created by selective logging can increase structural diversity within forest stands [42][43][44]. In addition, we also expect a more diverse spatial structure (though not analyzed here) in the transformation treatments especially when trees from enrichment plantings and from natural regeneration dominate the overstory and are able to self-regenerate.…”
Section: Species Composition and Forest Structurementioning
confidence: 83%
“…Advanced regeneration may be relatively secure, though seedlings established after gap formation can be ephemeral [42]. Sites with advanced regeneration are those with regeneration success in the years following gap formation.…”
Section: Future Prospects For Sustainable Forest Managementmentioning
confidence: 99%
“…The knowledge of species diversity is useful for establishing the influence of biotic disturbance and the state of succession and stability in the environment [36,37]. This species diversity index increases with the number of species in the community [6,38].…”
Section: Species Diversity and Evenness Indexmentioning
confidence: 99%